(untitled) (MIST International Journal of Science and Technology, 2020)
In the present study, the distribution pattern of the ultimate tensile strength of 304-grade stainless steel was investigated using a two-parameter Weibull distribution function. During tensile testing, it was observed that the ultimate tensile strength varied from specimen to specimen (ranges from 878 to 1006 MPa). The results have revealed that the distribution pattern of the tensile strength can be described by the two-parameter Weibull distribution equation. Moreover, the fracture statistics of the stainless steel were examined by plotting the survival probability of the specimen against the applied stress to the specimen. It has been observed that the relationship between the survival probability and the applied stresses can be described by the Weibull model. It also provides design engineers with a tool that will help them to present the necessary mechanical properties with confidence. MIJST, Vol. 8(2), December 2020: 1-6